2017
DOI: 10.1002/prot.25310
|View full text |Cite
|
Sign up to set email alerts
|

Designing dual inhibitors of Mdm2/MdmX: Unexpected coupling of water with gatekeeper Y100/99

Abstract: Mdm2 and MdmX share high structural similarity in their N-terminal domains, yet dual inhibitors are challenging to design due to differences in the conformations of the binding pockets, and notably of the proposed gatekeeper residue, Y100/99. Analysis of crystal structures and molecular dynamics (MD) simulations of complexes of Mdm2 and MdmX resulted in the identification of a water molecule with a long residence time that appears to be modulated by the conformation of Y100/99. These observations lead us to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Despite ~60% N-terminal structural identity between MDM2 and MDM4, there is significant distinction between their binding pocket conformation and dual inhibitors are proving challenging to design. To overcome the pocket distinctions and improve dual inhibitor efficiency, two new strategies are proposed: to impose upon MDM4 Tyr100/99 (where Tyr99 is the key residue for p53 engagement described in Section ‘ Phosphorylation/dephosphorylation .’) to stabilize MDM4 into an open state or to develop designs that are not affected by the conformation of these critical residues (Lee et al, 2017). In another study, adjacent MDM4 residue Leu98 was also identified for its determining role in staple-peptide engagement (Chee et al, 2017).…”
Section: Mdm4 Therapeutics and As A Prognostic Biomarkermentioning
confidence: 99%
“…Despite ~60% N-terminal structural identity between MDM2 and MDM4, there is significant distinction between their binding pocket conformation and dual inhibitors are proving challenging to design. To overcome the pocket distinctions and improve dual inhibitor efficiency, two new strategies are proposed: to impose upon MDM4 Tyr100/99 (where Tyr99 is the key residue for p53 engagement described in Section ‘ Phosphorylation/dephosphorylation .’) to stabilize MDM4 into an open state or to develop designs that are not affected by the conformation of these critical residues (Lee et al, 2017). In another study, adjacent MDM4 residue Leu98 was also identified for its determining role in staple-peptide engagement (Chee et al, 2017).…”
Section: Mdm4 Therapeutics and As A Prognostic Biomarkermentioning
confidence: 99%
“…Indeed, the first MDMX inhibitor, SJ172550, has been developed and shows a therapeutic effect (Reed et al, 2010). Moreover, dual inhibitors (like ATSP-7041) targeting both MDM2 and MDMX have also been developed (Chang et al, 2013; Lee et al, 2017b).…”
Section: Targeting P53 Modification Pathway For Disease Treatmentmentioning
confidence: 99%
“…have been developed and shown anticancer activity in vitro and in vivo. 16,47,[80][81][82][83][84][85][86] However, none of these inhibitors has been approved for clinical treatment. 7,87 Almost all of these inhibitors have been designed to reactivate wild-type p53 by inhibiting MDM2 and/or MDMX, and it is speculated that these inhibitors may have little or no inhibitory effect on human cancer cells with p53 mutation or p53 deletion.…”
Section: Dozens Of Mdmx Inhibitors and Mdmx/mdm2 Dual Inhibitorsmentioning
confidence: 99%
“…Dozens of MDMX inhibitors and MDMX/MDM2 dual inhibitors have been developed and shown anticancer activity in vitro and in vivo 16,47,80–86 . However, none of these inhibitors has been approved for clinical treatment 7,87 .…”
Section: The Roles Of Mdmx‐p53 Interplay In Human Cancermentioning
confidence: 99%